CYBERBULLYING ON TEENAGE ARTISTS AND ITS IMPLICATIONS ON INCREASING AWARENESS OF BULLYING - Indrayani, Sheira Ayu; Johansari, Citra Aulia (LITERA, 2019)
The cyberbullying in the comment section on social media tends to be a common phenomenon nowadays. Negative comments lead to bully being the dark side of social media, Instagram in particular, which is clearly visible in the comment section. Moreover, in uploaded photos of teen artists that have many followers on their Instagram. This study has three objectives. First, obtaining the lexical meaning of cyberbullying from negative comments in the comment section of some Indonesian teen artists uploaded photos on their personal Instagram. Second, describing the phenomenon of cyberbullying happened. Third, providing implications for increasing awareness of bullying based on findings. Purposive sampling was used to collect data by reading every single comment to get negative comments in the comment section. Semantic components were used to have the lexical meaning of cyberbullying, whereupon the result was classified into Willard (2007)'s cyberbullying types. The result reveals three things. First, the lexical component of cyberbullying consists of negative, rude, and not decent. Second, there are two types of cyberbullying occurred: harassment and cyberstalking. Third, the implication of this study is a tangible, sustainable, and comprehensive character building and sex education at all levels of society could be a solution to reduce cyberbullying. Keywords: cyberbullying, semantic components, social media PEMAKNAAN CYBERBULLYING PADA ARTIS REMAJA SERTA IMPLIKASINYA TERHADAP PENINGKATAN KESADARAN AKAN PERUNDUNGAN Abstrak Cyberbullying pada kolom komentar di media sosial cenderung menjadi fenomena yang biasa terjadi kini. Komentar negatif mengarah kepada perundungan menjadi sisi kelam media sosial, Instagram khususnya, yang terlihat jelas pada kolom komentar. Terlebih, pada berbagai unggahan foto para artis remaja dimana mereka memiliki banyak pengikut di laman Instagramnya. Penelitian ini memiliki tiga tujuan, yaiu untuk memperoleh makna leksikal cyberbullying dari komentar-komentar negatif pada kolom komentar beberapa foto artis remaja Indonesia yang diunggah di Instagram pribadi mereka; untuk menggambarkan fenomena cyberbullying yang terjadi; dan untuk memberikan implikasi terhadap peningkatan kesadaran akan perundungan berdasarkan temuan. Purposive sampling digunakan untuk mengumpulkan data yaitu dengan membaca satu per satu komentar guna menemukan komentar-komentar negatif pada kolom komentar artis-artis remaja. Analisis komponen makna digunakan untuk mengetahui makna leksikal cyberbullying, hasilnya diklasifikasikan ke dalam jenis cyberbullying Willard (2007). Hasil penelitian menemukan tiga hal. Pertama, komponen makna leksikal cyberbullying yang ditemukan adalah asusila, tidak baik, dan umpatan. Kedua, ada dua jenis cyberbullying yang terjadi: harassment dan flaming. Ketiga, implikasi dari penelitian ini adalah adanya pendidikan karakter dan pendidikan seks yang nyata, berkesinambungan, dan menyeluruh di seluruh lapisan masyarakat menjadi solusi untuk mengurangi cyberbullying. Kata kunci: cyberbullying, komponen makna, media sosial